Serine protease identification (in vitro) and molecular structure predictions (in silico) from a phytopathogenic fungus, Alternaria solani - Chandrasekaran, Murugesan; Chandrasekar, Raman; Sa, Tong-Min; Sathiyabama, Muthukrishnan (My University, 2013)
Serine proteases generally share a relatively high degree of sequence identity and play a major role in the diversity of biological processes. Here we focus on three-dimensional molecular architecture of serine proteases from Alernaria solani. The difference in flexibility of active binding pockets and electrostatic surface potential distribution of serine proteases in comparison with other fungal species is reported in this study. In this study we have purified a serine protease from the early blight pathogen, Alernaria solani. MALDI-TOF-MS/MS analysis revealed that protease produced by A. solani belongs to alkaline serine proteases. AsP is made up of 403 amino acid residues with molecular weight of 42.1kDa (Isoelectric point (pI)-6.51) and molecular formula C[subscript 1859]H[subscript 2930]N[subscript 516]O[subscript 595]S[subscript 4]. The follow-up research on the molecular structure prediction is used for assessing the quality of A. solani Protease (AsP). The AsP protein structure model was built based on its comparative homology with serine protease using the program, MODELER. AsP had 16 β-sheets and 10 α-helices, with Ser[superscript 350] (G347-G357), Asp[superscript 158] (D158-H169) and His[superscript 193] (H193-G203) in separate turn/coil structures. Biological metal binding region situated near the 6th-helix and His[superscript 193] residue is responsible for metal binding site. In addition, the calcium ion is coordinated by the carboxyl groups of Lys[superscript 84], Ile[superscript 85], Lys[superscript 86], Asp[superscript 87], Phe[superscript 88], Ala[superscript 89], Ala[superscript 90] (K84-A90) for first calcium (Ca[superscript 2+]) binding site and carbonyl oxygen atom of Lys[superscript 244], Gly[superscript 245], Arg[superscript 246], Thr[superscript 247], Lys[superscript 248], Lys[superscript 249], and Ala[superscript 250] (K244–A250), for second Ca[superscript 2+] binding site. Moreover, Ramachandran plot analysis of protein residues falling into most favored secondary structures were determined (83.3%). The predicted molecular 3D structural model was further verified using PROCHECK, ERRAT and VADAR servers to confirm the geometry and stereo-chemical parameters of the molecular structural design. The functional analysis of AsP 3D molecular structure predictions familiar in the current study may provide a new perspective in the understanding and identification of antifungal protease inhibitor designing.
Citation: Chandrasekaran, M., Chandrasekar, R., Sa, T., & Sathiyabama, M. (2014). Serine protease identification (in vitro) and molecular structure predictions (in silico) from a phytopathogenic fungus, Alternaria solani. Retrieved from http://krex.ksu.edu
Keywords: Alternaria solani; Serine protease; MODELER; PROCHECK; ERRAT; MALDI-TOF- MS/MS; Ramachandran plot; 3D molecular structural design